Analysis of the impact of the reliability of computer information systems on the environment of decision makers: an exploratory study of the opinions of a sample of managers in government organizations in Nineveh Governorate - Fadel Abbas Jassim Al Ameri; Muhammad Abd Hussein Al-Tai (Iraqi Journal for Administrative Sciences, 2024)
This paper aims to define the impact of relying on computerized. information system of the beneficiaries and the environment under which Such beneficiaries make their own decision. To fulfil this aim, the research has Taken up a hypothesized model which has embodied the independent Research variables and thesis thus availed the opportunity to test the research hypothesis within the framework of a sample consisting of (154) - Decision-makers who work at nine governmental organizations in the Governorate of Ninevah. Data was collected through a questionnaire. They were especially prepared for this purpose. The data was submitted to the statistical. Analysis, which led to the conclusions and necessary recommendations of the present paper.